Gentrification in new-build and old-build transit-oriented developments: the case of Bengaluru - Chava, Jyothi; Newman, Peter; Tiwari, Reena (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. Indian cities have seen substantial investment in building metro systems, with a few cities operating full-fledged metro. In the case of city of Bengaluru, the influx of public investment on transit and favourable zoning incentives are attracting around 26% of housing investment in transit-oriented developments (TODs). This paper examines whether such a large-scale influx of public and private capital is leading to gentrification in TODs. The findings indicate that the new housing projects in TODs are causing new-build gentrification, but the old build existing housing remains ungentrified. Towards mitigating gentrification issues, the paper recommends inclusive and equitable TOD strategies.